Risk factors influencing fracture characteristics in postoperative periprosthetic femoral fractures around cemented stems in total hip arthroplasty. (2021) - Jain, S.; Lamb, J.; Townsend, O.; Scott, C. E. H.; Kendrick, B.; Middleton, R.; Jones, S. A.; Board, T.; West, R.; Pandit, H.
No abstract available